The assessment of generation, transmission and distribution reliability (HLIII) in power system / Khalil Khusyairy Ibrahim - Ibrahim, Khalil Khusyairy (2006)
This project hightlights in the power system reliability in hierachial level III (HLIII). The power system reliability analysis is to ensure a reliable operation of distribution network system. Hierarchical level III is important to the power utility company to improve the design of distribution system in order to meet the customer demand and the changes of that design are fit to the system.